(untitled) (Journal of Guidance and Counselling Studies, 2021)
This paper is an attempt to examine the needs for ethical consideration in testing and evaluation, It argues that all in all, there are basically three areas of ethical consideration which pervade the literature; (i) Fairness of test-based decisions; (ii) The utility of tests for evaluating education and (iii) the implications of using test scores as labels for categorizing individuals. The paper also examines in some detail some other critical ethical issues like freedom from coercion, informed consent; limited deception; adequate debriefing; confidentiality and protection of privacy, It ends up by advocating monitoring of the use of these tools for testing and evaluation in order to avoid their abuse and misuse.